E-Marketing in Nigeria: Benefits, Challenges and Strategies - Salome, Ighomereho O; Ofunre, Iriobe C (Journal of Asian Business Strategy, 2019)
E-marketing is a marketing philosophy that has transformed the practice of marketing from traditional means to online platforms. It has changed the way and manner firms relate with their customers. Globally, there are variations in the practice and growth of e-marketing. As such, the paper discussed the benefits and challenges of e-marketing in Nigeria. It also examined strategies that can be adopted to enhance e-marketing by reviewing some models with the aim of drawing inferences and a direction for the growth and development of e-marketing in Nigeria. Content analysis was applied by reviewing literature on e-marketing. The paper indicates that the benefits of e-marketing range from global reach to new product development while the major challenges of e-marketing identified are inadequate Internet Infrastructure, cost of getting connected, unreliable power supply, inadequate number of knowledgeable staff and perceived lack of security. Moreover, e-marketing strategy framework comprising the Marketing Mix model, 4S model, Cox and Koelzer model as well as Granitz and Greene model were discussed. The paper concluded that Nigeria needs to improve her information and communications technology especially accessibility to internet infrastructure and security so that businesses and customers can avail themselves of the benefits of e-marketing.